2016
DOI: 10.1245/s10434-016-5155-x
|View full text |Cite
|
Sign up to set email alerts
|

Hiatal Hernia After Open versus Minimally Invasive Esophagectomy: A Systematic Review and Meta-analysis

Abstract: Hiatal hernia (HH) is an infrequent yet potentially life-threatening complication after esophagectomy. Several studies have reported the incidence of this complication after both open and minimally invasive esophagectomy (MIE). This meta-analysis aimed to determine the pooled incidence of HH after both types of esophagectomy and, importantly, to provide insight in the outcome of subsequent HH repair. A systematic search was performed of the PubMed, Embase, CINAHL, and Cochrane databases. Article selection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 30 publications
4
99
0
Order By: Relevance
“…Thus, the true incidence of HH is most likely between 7% and 10%. These numbers are comparable to a recent meta-analysis and a recent UK study [18,19] that reported an incidence of 5% and 6%, respectively. HH after esophagectomy will become an increasing problem as cancer survival improves.…”
Section: Occurrencesupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the true incidence of HH is most likely between 7% and 10%. These numbers are comparable to a recent meta-analysis and a recent UK study [18,19] that reported an incidence of 5% and 6%, respectively. HH after esophagectomy will become an increasing problem as cancer survival improves.…”
Section: Occurrencesupporting
confidence: 88%
“…The influence of MIE on the occurrence of HH is currently an important topic of debate. A recent meta- analysis of 6,058 patients found a higher incidence of a symptomatic HH after MIE (4.5%) compared with after open esophagectomy (1.0%) [18]. A frequently reported explanation is the reduced formation of peritoneal adhesions after MIE, although there is no evidence to prove this theory.…”
Section: Occurrencementioning
confidence: 99%
“…A hiatus hernia has an increased incidence after minimally invasive approach (7-9%) compared to open esophagectomy possibly due to the reduction in postoperative adhesion formation and is becoming more relevant due to the increase in survival rate (74). The laparoscopic approach can be used to treat a hernia and the use of a mesh should avoid the risk of vascular injury of the gastric conduit (75).…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Postoperative diaphragmatic hernia (PDH) is a well-known complication of esophageal cancer surgery that can be associated with significant morbidity and mortality [ 1 6 ]. The risk of developing PDH after esophagectomy seems to be much higher when minimally invasive techniques are employed [ 2 5 , 7 ]. Several mechanisms and risk factors may be involved in the pathogenesis of PDH, and many measures have been suggested in order to minimize its occurrence, although little evidence is available on this regard [ 1 11 ].…”
Section: Introductionmentioning
confidence: 99%